CSR Communication Relationship Management of Djarum Foundations’s Social Service in the LKSA Program for Orphanages in Kudus - Salwa Talitha Zahra; Riski Apriliani (Jogjakarta Communication Conference (JCC), 2026)
Companies have an important role in their surrounding environment through Corporate Social Responsibility (CSR). PT Djarum is one of the private companies that established the Djarum Foundation as a CSR foundation, one of which is engaged in social activities, namely Bakti Sosial. This study focuses on the Program for Improving the Quality of Child Social Welfare Institutions (LKSA) because the fulfillment of children's rights is in line with the objectives of the Sustainable Development Goals (SDGs). This study uses Relationship Management Theory, which aims to determine how the Djarum Foundation's Bakti Sosial CSR communication relationship management in the LKSA program affects the orphanages it supports in Kudus. This study uses qualitative methods and data collection techniques through Focus Group Discussions (FGD) and In-Depth Interviews consisting of 36 individuals. The informant selection technique uses purposive sampling. Data validity was tested using source triangulation. The data analysis technique used was the Miles and Huberman model, which consists of three stages, namely data reduction, data presentation in the form of descriptive narratives, and conclusion drawing or verification. The results of this study explain that the management of the Djarum Foundation's Bakti Sosial CSR relationships with LKSA in Kudus has implemented the dimensions of trust, commitment, satisfaction, and control mutuality, which are manifested through two-way communication, transparency, responsibility, and program consistency.